On the Viability of Solutions to Conformable Stochastic Differential Equations (Journal of Partial Differential Equations, 2024)
The viability of the conformable stochastic differential equations is studied.Some necessary and sufficient conditions in terms of the distance function to $K$ aregiven. In addition, when the boundary of $K$ is sufficiently smooth, our necessary andsufficient conditions can reduce to two relations just on the boundary of $K.$ Lastly, anexample is given to illustrate our main results.
Keywords: Viability; conformable derivatives; conformable stochastic differential equation.